White teachers, diverse classrooms : creating inclusive schools, building on students' diversity, and providing true educational equity - Landsman, Julie; Lewis, Chance W. (Chance Wayne), 1972- (Sterling, Va. : Stylus Pub., 2011)
"The point of departure for this new edition, as it was for the first, is the unacceptable reality that, for students of color, school is often not a place to learn but a place of low expectations and failure. This second edition has been considerably expanded with chapters that illuminate the Asian American, Native American, and Latina/o experience, including that of undocumented students, in our schools. These chapters offer insights into the concerns and issues students bring to the classroom. They also convey the importance for teachers, as they accept difference and develop cultural sensitivity, to see their students as individuals, and avoid generalizations. This book encourages reflection and self-examination, demonstrates what it means to recognize often-unconscious biases, confront institutional racism where it occurs, surmount stereotyping, adopt culturally relevant teaching, connect with parents and the community, and integrate diversity in all activities. Replete with examples from practice and telling insights that will engage teachers in practice or in service, this book should have a place in every classroom in colleges of education, and in all schools." --from back cover.
Includes bibliographical references and index.
Keywords: Multicultural education -- United States; Minorities -- Education -- United States; Race awareness -- Study and teaching -- United States; Teachers, White -- United States; Multiculturalism -- United States